Style of practice and assortative mating: a recursive probit analysis of cesarean section scheduling in Italy - Daniele Fabbri; Chiara Monfardini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
We study practice variation in scheduling of cesarean section delivery across public and private hospitals in Italy. Adopting a novel perspective, we look at the role played by patients' preferences for the treatment. The recursive probit model is revisited as a useful tool to assess the presence of assortative mating of patients and provider driven by style of practice. According to our evidence the propensity to scheduling a cesarean section is codetermined with patient self-sorting into hospital types. We measure a significantly higher inclination to practice cesarean section scheduling in private hospitals and conclude that assortative mating is of minor relevance in our case, even if we cannot exclude it to be present
Keywords: 330; Krankenhaus; Italien; Schwangerschaft; Probit-Modell